THE EFFECTIVENESS OF CRIMINAL LAW POLICIES ON RELIGIOUS ABUSE AND BLASPHEMY CRIMES - Yudhi Achmad Bashori (IAIN Bone, 2020)
ABSTRACTCriminal law policy is one of the instruments of the rule of law - specifically Indonesia - to realize security and order in the lives of every citizen. One of the crimes that often trigger conflicts between the communities is acts related to religion. This is because anthropologically, Indonesian communitiesare known as religious communities. So that if there is an